Current and Future Challenges in the Delivery of Mental Healthcare during COVID-19 - Gautam, Mohan (SN Compr Clin Med, 2020)
The USA is in the midst of the COVID-19 pandemic. We assess the impact of COVID-19 on psychiatric symptoms in healthcare workers, those with psychiatric comorbidities, and the general population. We highlight the challenges ahead and discuss the increased relevance of telepsychiatry. We analyzed all available literature available as of March 25, 2020, on PubMed, Ovid Medline, and PsychInfo. We utilized the MeSH term “covid AND (psychiatry OR mental health)” and included all articles. Duplicates were removed resulting in 32 articles, of which 19 are cited. Four additional references are included to examine suicide data. During the review process, an additional 7 articles were identified which are also included. Frontline healthcare workers are currently experiencing increased psychiatric symptoms and this is more severe in females and nurses. Non-frontline healthcare workers, as well as the general population, are experiencing vicarious traumatization. People with psychiatric comorbidities, and the general population, face increased psychiatric symptom burden. Migrant workers, the elderly, children, and the homeless may be disproportionately impacted. Suicide rates may be impacted. The COVID-19 pandemic has resulted in a severe disruption to the delivery of mental healthcare. Psychiatric facilities are facing unprecedented disruptions in care provision as they struggle to manage an infected population with comorbid psychiatric symptoms. Telepsychiatry is a flawed but reasonable solution to increase the availability of mental healthcare during COVID-19.